Judicious management of pinna keloids: our experience with combination therapy - Mathews, Sunil; Jose, Asha T.; Gangwar, Varun; Vadivu, Arumugam S.; Nandhan, Raghu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Keloids occur as a result of overgrowth of fibrous tissue following healing of a cutaneous injury and they cause aesthetic issues when they appear on the exposed parts of the body, especially the face. Keloids are difficult to treat, with a high recurrence rate. There are several treatment modalities for management of keloids, though no single modality is completely effective. Most commonly used treatment modalities are intra-lesional steroids, surgical excision, pressure application, silicone gel sheets, 5-fluorouracil (5-FU), cryotherapy, radiation therapy, laser therapy or a combination of these modalities. The aim of the study was to analyse the causes of development of keloids on the pinna and evaluated the outcomes of various treatment modalities applied. It focused on assessing the clinical efficacy of combined surgical excision of pinna keloids with serial steroid injections to prevent recurrence, in comparison to monotherapy with intra-lesional steroid injections alone. Methods: A retrospective review based on medical records was done for 18 patients with keloid of pinna, who were treated with either monotherapy or combination therapy. Results: Satisfactory low recurrence rates were observed with meticulous surgical excision followed by serial steroid injections (18.2%), as compared to monotherapy with serial steroid injections alone (71.4%), and these comparative results were statistically significant at p<0.05 in the cohort. Conclusions: A judicious plan for management for pinna keloids is necessary in order to achieve the best functional and cosmetic outcomes, while reducing the recurrence rates to a minimum. Following a combination of interventions has proved safe and effective for managing this challenging entity.